"Is Austria a Catholic Country?": Trust and Intersubjectivity in Postconflict Northern Ireland. Issue 2 (3rd July 2021) - Reinisch, Dieter
ABSTRACT: Media pundits, politicians, and academic observers have frequently described the Northern Irish Troubles as a religious conflict, a description the Irish republican actors of the conflict reject. In 2009 and 2011, I interviewed twenty-five former Irish republican women activists. Other scholars have argued that the emotions, feelings, and subjective experiences of the researcher can have several roles and functions and, thus, shape our research interests and decisions. Similarly, the interviewer's presence, as much as the narrator's perceptions, will shape the story the narrators tell. Based on these considerations, I discuss how the Irish republican women I interviewed projected their own Catholic convictions on me, despite stressing that they were not overly religious or even practicing Catholics. These women acknowledged that as I was Austrian, I was a "neutral outsider to the conflict" (as one woman put it), but nevertheless, they projected a supposed shared affinity on me. These projections shaped their answers during the interviews. Furthermore, while these women emphasized that their political motivation for Irish republican activities was not religiously driven, they were raised in a Catholic environment. Thus, these subjective experiences shaped their answers and attitudes towards the interviewer. In essence, this article examines, first, how Catholic convictions were projected on the interviewer by narrators in oral history projects on the Northern Ireland conflict and, second, what roles and functions these religious projections served during the interview process.